2013
DOI: 10.1002/dvdy.23935
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for N‐Cadherin linked c‐Src and fyn kinases in lens development

Abstract: Background Src family tyrosine kinases (SFKs) are often coincidently expressed but few studies have dissected their individual functions in the same cell during development. Using the classical embryonic lens as our model we investigated SFK signaling in the regulation of both differentiation initiation and morphogenesis, and the distinct functions of c-Src and Fyn in these processes. Results Blocking SFK activity with the highly specific inhibitor PP1 induced initiation of the lens differentiation program b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 73 publications
(136 reference statements)
4
19
0
Order By: Relevance
“…It might be important to study other molecules that are involved in the restricted activation of Src and cortactin that establish organized meridional rows prior to fiber cell elongation and differentiation. It has recently been reported that Fyn, another member of the Src family, is utilized to regulate N-cadherin junctions in the chick lens fiber cell (Leonard et al, 2013). Since the disruption of Src −/− lens fiber cells is less severe than that of Epha2 −/− lens fiber cells (Fig.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…It might be important to study other molecules that are involved in the restricted activation of Src and cortactin that establish organized meridional rows prior to fiber cell elongation and differentiation. It has recently been reported that Fyn, another member of the Src family, is utilized to regulate N-cadherin junctions in the chick lens fiber cell (Leonard et al, 2013). Since the disruption of Src −/− lens fiber cells is less severe than that of Epha2 −/− lens fiber cells (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Studies in chick and quail lens explant models suggest that Src might be involved in posterior capsular cataracts and cortical cataracts (Leonard et al, 2013;Walker et al, 2007;Zhou et al, 2007;Zhou and Menko, 2004). However, Src has not been reported to be directly associated with human cataracts.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…E- and N-cadherins are localized at the apical and lateral sides of the lens epithelial cells to maintain their polarity and adhesion to each other, which also requires the RapGAP protein Sipa1l3 and ephrin-A5 signaling [154, 222225]. In the lens fiber cells, N-cadherin promotes cell elongation and morphogenesis by activating the Src family kinase Fyn, intersecting with EphA2 receptor tyrosine kinases that induce phosphorylation of the Src and F-actin binding protein cortactin to control actin assembly and fiber cell alignment [226, 227]. Also at the lateral side of the lens fiber cells, the gap junction protein Cx50 (Gja8) not only forms channels for ion and metabolite exchange, but also negatively regulates E3 ubiquitin ligase Skp2 to prevent degradation of the cell cycle inhibitor Cdkn1b/p27, promoting cell cycle exit and differentiation [228].…”
Section: Reiterative Use Of the Same Genes And Signaling Pathways Dirmentioning
confidence: 99%
“…3. Study the separated OAZ and CMZ fractions for molecular analysis such as RNA-Seq 24 or biochemical analysis such as western blot or coimmunoprecipitation 23,25 .…”
Section: Separation Of the Centralmentioning
confidence: 99%